Новые данные о субмаринной разгрузке подземных вод в районе м. Айя (Крым) - Иванов, В.А.; Прусов, А.В.; Юровский, Ю. Г. (Видавничий дім "Академперіодика" НАН України, 2008)
The study reports the data of in situ observations of the submarine ground water discharge collected in September 2007 in the region of the cape Aya (Crimea, Ukraine). We used a special equipment designed in Marine Hydrophysical Institute (Ukraine) to measure the current speed, temperature, water salinity, turbidity, and silica concentration in a grotto and the area around it. The evaluation of the submarine ground water discharge is provided.